"East Indian Girl", Trinidad, B.W.I. - (:unkn) unknown (Y. De Lima and Co. Ltd. [Printed in Great Britain], 2008)
Photograph of a young woman of East Indian origin, wearing a sari and adorned with necklaces, nose rings, armlets and bangles.
Colour: Brown and White; Style: Portrait; Other: Bordered, Divided
Keywords: Postcards; East Indians--Trinidad and Tobago; Jewelry--India; Trinidad and Tobago; Ethnic costume--India; Girls--Trinidad and Tobago; Young women--Trinidad and Tobago